Penerapan Server VoIP Trixbox untuk Mendukung Komunikasi di Sekolah Asrama Putri Ma'hadul Qur'an - Imroatin Arifa Aini; Komang Nitari Atika Virda Hasan; Rosiana Lestari; Abdus Samad (POLITEKNIK PIKSI GANESHA, 2026)
Communication barriers are often the main cause of coordination issues in Islamic boarding schools, as experienced by the Ma’hadul Qur’an (MQ) Girls’ Dormitory at the Salafiyah Syafi’iyah Sukorejo Islamic Boarding School. Operational challenges, such as running out of phone credit or unanswered calls, frequently hinder administrators when making a series of calls (hunting)to confirm the study session schedule with the ustadz, ustadzah, and Muallim. In addition, the flow of information from the central dormitory, coordination with the girls’ tahfidz administrators, and cross-sectoral communication with the MQ boys’ administrators tends to be slow. As a solution, this study implemented Voice ovel Internet Protocol (VoIP) technology using a Trixbox server. Through this infrastructure, all members of the administration can communicate with one another via the local Wi-Fi network without incurring call charges. The hunting system was also optimized so that emergency calls coordination between dormitories can be connected immediately and effectively. The result of the implementation demonstrate that the use of Trixbox VoIP has reduced communication bureaucrary at MQ girls, accelerated the coordination of teaching activities, and significantly reduced the dormitory’s operational communication budget.